1997
DOI: 10.1093/jn/127.5.717
|View full text |Cite
|
Sign up to set email alerts
|

Acarbose Enhances Human Colonic Butyrate Production

Abstract: Earlier studies suggest that butyrate has colonic differentiating and nutritional effects and that acarbose increases butyrate production. To determine the effects of acarbose on colonic fermentation, subjects were given 50-200 mg acarbose or placebo (cornstarch), three times per day, with meals in a double-blind crossover study. Fecal concentrations of starch and starch-fermenting bacteria were measured and fecal fermentation products determined after incubation of fecal suspensions with and without added sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
82
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 21 publications
7
82
0
Order By: Relevance
“…The dose-response effect of acarbose on the risk of colorectal cancer we observed concords with a previous clinical biomarker study demonstrating that each dose (50-200 mg) of acarbose enhances colonic butyrate production, which has colonic differentiating and nutritional effects (28). In the current study, the associations persisted after adjustment for the confounding factors.…”
Section: Discussionsupporting
confidence: 62%
“…The dose-response effect of acarbose on the risk of colorectal cancer we observed concords with a previous clinical biomarker study demonstrating that each dose (50-200 mg) of acarbose enhances colonic butyrate production, which has colonic differentiating and nutritional effects (28). In the current study, the associations persisted after adjustment for the confounding factors.…”
Section: Discussionsupporting
confidence: 62%
“…These concentrations of BT chosen are well within the physiological range of concentrations of this compound in the human colon, since the concentration of short-chain fatty acids in the human colon may reach 70 -130 mM after digestion of dietary fiber, with 20 -30% of these corresponding to BT (9,47), and BT concentrations in human feces were found to range from 11 to 25 mM (30,66).…”
Section: Chronic Treatment Of the Cellssupporting
confidence: 62%
“…The Caco-2 cell line was obtained from the Deutsche Sammlung von Mikroorganismen and Zellkulturen (Braunschweig, Germany) and was used between passage numbers [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71]. The cells were maintained in a humidified atmosphere of 5% CO 2-95% air and were grown in Minimum Essential Medium (Sigma, St. Louis, MO) containing 5.55 mM glucose and supplemented with 15% fetal calf serum, 25 mM HEPES, 100 U/ml penicillin, 100 g/ml streptomycin, and 0.25 g/ml amphotericin B (all from Sigma).…”
Section: Caco-2 Cell Culturementioning
confidence: 99%
“…24) Acarbose treatment in rats contributes to a higher level of SCFA in the colon, 4) and Weaver et al have also showed increased colonic butyrate production in human studies of acarbose supplementation. 25) SCFAs are an indispensable waste product to the microbial community, 26) meanwhile for colonic epithelium and immune modulation SCFAs especially butyrate are thought to be beneficial. 27,28) The short-chain fatty acid receptors Free Fatty Acid Receptor 2 (FFA2 or GPR43) and Free Fatty Acid Receptor 3 (FFA3 or GPR41) are activated by acetate, propionate and butyrate 29) but the metabolic function of them remains controversial.…”
mentioning
confidence: 99%